A novel bi-material negative stiffness metamaterial in sleeve-type via combining rigidity with softness. (15th April 2021) - Zhu, Shaowei; Wang, Bing; Tan, Xiaojun; Hu, Jiqiang; Wang, Lianchao; Zhou, Zhengong; Chen, Shuai
Abstract: Negative stiffness metamaterials (NSM) can dissipate mechanical energy repeatedly based on a "snap-though" mechanism. However, this mechanism is only effective when many NSM cells are arranged in series or such cell is assembled with a spring. Limits of the mechanism bring a challenge to improve the energy dissipation capacity of the NSM. Here, a novel bi-material NSM in sleeve-type (BMST-NSM) is designed which can dissipate mechanical energy even if the metamaterial is only composed of one negative stiffness cell. The quasi-static loading–unloading experiment is conducted to investigate the characteristics of BMST-NSMs; a multilinear model is presented to characterize the load–displacement curve of BMST-NSMs; and the finite element method (FEM) is used to study the characteristic of strain distribution in BMST-NSMs. Research results show that BMST-NSM can be tailored to be recoverable or multi-stable through parameter design. BMST-NSMs are also tested under different loading speeds and high cyclic loading, which shows that the recoverable BMST-NSM is of good reusability and energy dissipation ability. Moreover, it indicates that BMST-NSM can exhibit a high energy absorption capability within a certain limited displacement range. The presented BMST-NSM has great prospects in low ultra-low frequency vibration isolation and energy dissipation in impacting protection.